The complex concept of sustainable of diversity management: … and why forming policies in this area is far from straightforward. Issue 5 (13th July 2015) - Best, Simon; Soyode, Alistair; Muller-Camen, Michael; Boff, Andrew
Abstract : Purpose: – Explores the notion of sustainable diversity-management practices. Design/methodology/approach: – Summarizes research into the sustainability of diversity management across four countries and provides examples of efforts to maintain high levels of diversity. Findings: – Looks at the activities of Africa House, an organization that develops business links with Africa, and of Bright Entertainment Network (BEN) Television, which is a television station that caters primarily for ethnic minorities. Social implications: – Highlights the complexity of diversity and so the difficulty of legislating in this area. Originality/value: – Explains that employees can also stifle attempts to engage in sustainable diversity management policies. A lack of understanding of local laws or language, or through limited social contacts, can prevent full participation by employees.